Thermal effects of AISI 304-L stainless steel after laser irradiation - Anderson Kenji Hirata; Claudio Luis dos Santos; Helder de Paula Vicente; Paulo Paiva Oliveira Leite Dyer; Getulio de Vasconcelos (The Journal of Engineering and Exact Sciences)
Laser Directed Energy Deposition (L-DED) is one of the Additive Manufacturing (AM) techniques that has emerged in recent years, and it is one of the disruptive technologies of the Industry 4.0. The selection of welding parameters of the L-DED system is critical for obtaining the desired results in metal deposition, however, due to its intrinsic nonlinear behavior in the process, the suitable choices need to be investigated. In this work it is presented an experimental setup to study the thermal effects on the metal substrate during the process of irradiation. With 40% and 60% of laser beam power, the irradiation results showed only a change in color, but no change in roughness or melting pool was formed. However, with 68% of laser power, a considerable increase of the substrate average temperature with values of more than 100°C at each adjacent track created was observed. The heat affected zone (HAZ) in this sample is expanded in both length and width as the temperature rises due the accumulation of heat during the irradiation process. It is concluded that the temperature of the substrate and other related process variables to be investigated must be controlled to achieve the desired bead formation.